Efficacy and safety of different radiotherapy doses in neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer: A retrospective study - Xu, Yuyan; Zou, Haizhou; Shao, Zhenyong; Zhang, Xuebang; Ren, XiaoLin; He, Huijuan; Zhang, Dahai; Du, Dexi; Zou, Changlin (Frontiers in Oncology, 2023)
Background This study aims to compare the efficacy and safety of neoadjuvant chemoradiotherapy (nCRT) with different radiotherapy doses (45Gy and 50.4Gy) in patients with locally advanced rectal cancer (LARC). Methods Herein, 120 patients with LARC were retrospectively enrolled between January 2016 and June 2021. All patients underwent two courses of induction chemotherapy (XELOX), chemoradiotherapy, and total mesorectum excision (TME). A total of 72 patients received a radiotherapy dose of 50.4 Gy, while 48 patients received a dose of 45 Gy. Surgery was then performed within 5-12 weeks following nCRT. Results There was no statistically significant difference between the baseline characteristics of the two groups. The rate of good pathological response in the 50.4Gy group was 59.72% (43/72), while in the 45Gy group achieved 64.58% (31/48) (P>0.05). The disease control rate (DCR) in the 50.4Gy group was 88.89% (64/72), compared to 89.58% (43/48) in the 45Gy group (P>0.05). The incidence of adverse reactions for radioactive proctitis, myelosuppression, and intestinal obstruction or perforation differed significantly between the two groups (P<0.05). The anal retention rate in the 50.4Gy group was significantly higher in contrast to the 45Gy group (P<0.05). Conclusions Patients receiving a radiotherapy dose of 50.4Gy have a better anal retention rate but also a higher incidence of adverse events such as radioactive proctitis, myelosuppression, and intestinal obstruction or perforation, and a comparable prognosis to patients treated with a radiotherapy dose of 45Gy.